MENUMBUHKAN JIWA SOSIAL SISWA MELALUI PEMAHAMAN SURAH AL-MA’UN DI LEMBAGA PENDIDIKAN ISLAM - Maisaroh, Tita; Mujrimin, Bayu; Supriadi (MUHAFADZAH: Jurnal Ilmiah Bimbingan dan Konseling Islam, 2025)
Surah al-Ma’un is one of the chapters in the Qur’an that carries a strong social message, particularly in shaping a caring and compassionate character. In the context of Islamic educational institutions, the values contained in Surah al-Ma’un are highly relevant to be instilled in students from an early age in order to cultivate social awareness and concern for their surroundings. This study aims to examine the implementation of Surah al-Ma’un understanding in teaching and its impact on the development of students’ social character. The research uses a qualitative-descriptive approach with observation, interview, and documentation techniques conducted in several Islamic educational institutions. The results show that a deep understanding of the meanings in Surah al-Ma’un, especially the verses emphasizing the importance of feeding the poor and not neglecting orphans, can foster empathy, care, and a spirit of sharing among students. The integration of these values through habituation activities, thematic learning, and teacher role modeling plays a vital role in shaping students’ social character. Thus, Surah al-Ma’un is not only understood theoretically but also internalized through real-life actions in students' daily lives within Islamic education settings.